Poor response to artesunate treatment in two patients with severe malaria on the Thai-Myanmar border - Phyo, A; Win, K; Thu, A; Swe, L; Htike, H; Beau, C; Sriprawat, K; Winterberg, M; Proux, S; Imwong, M; Ashley, E; Nosten, F (BioMed Central, 2018)
Background Malaria has declined dramatically along the Thai–Myanmar border in recent years due to malaria control and elimination programmes. However, at the same time, artemisinin resistance has spread, raising concerns about the efficacy of parenteral artesunate for the treatment of severe malaria. Case presentation In November 2015 and April 2017, two patients were treated for severe malaria with parenteral artesunate. Quinine was added within 24 h due to an initial poor response to treatment. The first patient died within 24 h of starting treatment and the second did not clear his peripheral parasitaemia until 11 days later. Genotyping revealed artemisinin resistance Kelch-13 markers. Conclusions Reliable efficacy of artesunate for the treatment of severe malaria may no longer be assured in areas where artemisinin resistance has emerged. Empirical addition of parenteral quinine to artesunate for treatment is recommended as a precautionary measure.